“Vivere da fratelli”. L’associazionismo politico nell’Italia del triennio (1796-1799) - Guerra, Alessandro (Studi Politici, 2022)
The arrival of the Armée d’Italie in 1796 stimulated the birth of a strong democratic movement in Italy. That movement was expressed in the most original form in the associative political space. Through the rich panorama of democratic sociality, a conscious public opinion arose and contributed decisively to the formation of the first nucleus of a unitary policy.